Who Wants to be Legible? Digitalization and Intergroup Inequality in Kenya - Lisa Garbe; Nina McMurry; Alexandra Scacco; Kelly Zhang (Comparative Political Studies, 2024)
Governments across the Global South have begun introducing biometric IDs (eIDs) in an attempt to improve citizen-state legibility. While such initiatives can improve government efficiency, they also raise important questions about citizen privacy, especially for groups with a history of mistrust in the state. If concerns about increased legibility produce differential uptake or changes in political behavior, eID initiatives may exacerbate societal inequalities. In a conjoint experiment with 2,072 respondents from four Kenyan regions, we examine how perceptions of and willingness to register for eID under different policy conditions vary across politically dominant, opposition, and “securitized” (heavily policed) ethnic groups. We find meaningful group-level variation in support for specific policy features, and suggestive evidence that policies facilitating surveillance may discourage opposition political participation. Our most surprising finding, however, is that there is such broad support for expanded legibility. The promise of access to government services appears to outweigh other considerations.
https://doi.org/10.7910/DVN/EGVC5Q
Keywords: 320; legibility; surveillance; digitalization; Kenya; political inequality; ethnic politics